SEAGRASS POPULATION CONNECTIVITY IN THE SOUTH CHINA SEA - Hernawan, Udhi Eko (Research Center for Oceanography - Indonesian Institute of Sciences (LIPI), 2018)
Seagrass plays important ecological roles and ecosystem services, yet degrading alarmingly in the South China Sea (SCS), one of the largest marginal seas of the Western Pacific. As connectivity is a vital component in population persistence, understanding of connectivity is of importance for effective seagrass conservation management. In the South China Sea, our understanding of connectivity is mainly based on studies in fishes and invertebrates. Connectivity in seagrass populations, on the other hand, is still poorly investigated. In this review, I predict that genetically structured population of seagrass is likely to occur in the SCS. Future research on seagrass connectivity should include (i) investigation on the pattern of connectivity at a local and broader-regional scale, and (ii) investigation on processes involved in the seagrass connectivity. These investigations are aimed to improve our knowledge of seagrass connectivity and to contribute in providing a solid framework for seagrass restoration/transplantation and spatial planning of seagrass management.